2013
DOI: 10.4318/tjg.2013.0568
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the speed of eating on acid reflux and symptoms of patients with gastroesophageal reflux disease

Abstract: Girifl ve Amaç: Gastroözofageal reflü ataklar›n›n h›zl› yenilen yemek sonras› artt›¤›na inan›lmakta ve hastalara yavafl yemeleri önerilmektedir. Kuvvetli bir bilimsel veriye dayand›r›lmasa da bu inan›fl temel al›narak hastalara yavafl yemek yemeleri öner-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…In our previous study, we compared the effect of fast food intake vs. slow food intake on reflux episodes using pH‐monitoring in patients with GOR. No significant difference was shown between the parameters (number of refluxes, time of reflux episodes, number of symptoms, primarily heartburn or acid regurgitation) obtained in the fast‐eating period compared to the slow‐eating period 11 …”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In our previous study, we compared the effect of fast food intake vs. slow food intake on reflux episodes using pH‐monitoring in patients with GOR. No significant difference was shown between the parameters (number of refluxes, time of reflux episodes, number of symptoms, primarily heartburn or acid regurgitation) obtained in the fast‐eating period compared to the slow‐eating period 11 …”
Section: Discussionmentioning
confidence: 87%
“…10 We previously used 24-hour intraoesophageal pH monitoring to show that slow eating increases the number of acid reflux events. 11 Because 24-hour intraoesophageal pH monitoring only measures refluxes that are acid, we performed the present study using multichannel intraluminal impedance-pH to determine the impact of rapid vs. slow food intake on GORD patients. The aim of this study is to investigate the effect of eating speed on gastro-oesophageal reflux episodes and to determine a scientific basis for recommendations concerning the eating speed of patients with reflux.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Skipping breakfast was positively associated with constipation in Japanese university students [19]. In contrast, no association between skipping breakfast and GERD was found in a Turkish study [32] and another Japanese study [33]. Several studies found a positive association between unhealthy eating behaviors and digestive diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Skipping breakfast was positively associated with constipation in Japanese university students [18]. In contrast, no association between skipping breakfast and GERD was found in a Turkish study [31] and another Japanese study [32]. Several studies found a positive association between unhealthy eating behaviors and digestive diseases.…”
Section: Discussionmentioning
confidence: 99%